Advanced exergy-based performance enhancement of heat pump space heating system. (15th August 2020) - Voloshchuk, Volodymyr; Gullo, Paride; Sereda, Volodymyr
Abstract: Heat pump technologies for space heating can contribute to substantial economic, environmental and energy saving benefits. However, their performance is generally evaluated through energy-based methods. The distinguish feature of the exergy-based approaches is that, unlike to the energy-based ones, they are more powerful and convenient tools for developing, evaluating, understanding and improving energy conversion systems without the need of additional analysis and iterations. Exergy-based estimation (i.e. exergy, exergeconomic and exergoenvironmental analysis) has been applied to an air-source R134a heat pump unit for space heating, being this solution widely employed worldwide. According to the results obtained 63% and 20% of the avoidable exergy destruction within the heat pump belongs to inefficiencies within the evaporator and the condenser respectively. For the investigated heat pump the biggest parts of the avoidable cost associated with investment expenditures and exergy destruction belong to the compressor (56%) and the evaporator (35%). For the compressor this is caused mostly by capital investment and for the evaporator - mostly by its thermodynamic inefficiency. About 70% of the total avoidable environmental impact associated with construction and exergy destruction belongs to the evaporator and can be decreased mostly by improving thermodynamic efficiency of this component. For simultaneous improvement of thermodynamic, economic and environmental performance of the investigated solution the irreversibilities occurring in the evaporator and in the condenser has to be decreased. In addition, it is found that, to achieve such a target, reducing the temperature differences through both heat exchangers is a more suitable measure compared to the replacement of the existing emission heating system. The derived exergy-based conclusions are confirmed with objective functions based on a set of energy, economic and environmental criteria. Compared with the initial case the improved solution provides the reduced value of annual exergy destruction by 31%. The annual cost of exergy of the product of the improved system is also decreased by several percent. The annual environmental impact associated with the product of the system is decreased by 9.5%. Highlights: Exergy-based analysis has been applied to an air-source heat pump for heating. The system performance has beeninvestigated based on its off-design operational modes. Reducing the irreversibilities through the evaporator and condenser has been proposed. The thermodynamic, economic and environmental performance of the system has beenevaluated.